2015
DOI: 10.1111/jfpp.12441
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Treatment of CaCl2 , Citric Acid and Sorbitol Reduces Loss of Quality of Button Mushroom (Agaricus Bisporus ) during Postharvest Storage

Abstract: Because of the short shelf life of button mushroom, its long-term preservation efforts gained momentum. In this study, we evaluated the efficiency of chemical dips for quality maintenance of button mushrooms during storage and compared three different treatments: water (CK), T1 (2.5% w/v CaCl2, 0.5% w/v citric acid) and T2 (2.5% w/v CaCl2, 0.5% w/v citric acid, 3% w/v sorbitol). Changes in weight, firmness, color, malondialdehyde (MDA), hydrogen peroxide (H2O2), hydroxyl radical ( -OH), superoxide dismutase (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In another report, γ‐irradiation was applied for the preservation of mushrooms, which caused PAL excitation and total phenolic accumulation (Benoît et al ., ). Research has shown that increases in resistance‐related enzymes activity effectively delay the softening of edible fungi (Jiang et al ., ; Khan et al ., ). In this study, the activities of PAL, catalase and SOD in the ultrasonic‐treated shiitake mushrooms were higher than in the untreated mushrooms.…”
Section: Discussionmentioning
confidence: 97%
“…In another report, γ‐irradiation was applied for the preservation of mushrooms, which caused PAL excitation and total phenolic accumulation (Benoît et al ., ). Research has shown that increases in resistance‐related enzymes activity effectively delay the softening of edible fungi (Jiang et al ., ; Khan et al ., ). In this study, the activities of PAL, catalase and SOD in the ultrasonic‐treated shiitake mushrooms were higher than in the untreated mushrooms.…”
Section: Discussionmentioning
confidence: 97%
“…Jiang et al (2010b) suggested that changes in firmness were due to differences in cellulose and chitin concentrations. Increased antioxidant enzyme activities, such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase (POD) and glutathione reductase (GR), can delay softening (Jiang et al, 2010a;Khan et al, 2015). Increased antioxidant enzyme activities, such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase (POD) and glutathione reductase (GR), can delay softening (Jiang et al, 2010a;Khan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zivanovic et al (2000) demonstrated that the intercellular space at the pilei surface, hyphae shrinkage, central vacuole disruption, and loss of proteins and polysaccharides cause softening of Agaricus bisporus. Increased antioxidant enzyme activities, such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase (POD) and glutathione reductase (GR), can delay softening (Jiang et al, 2010a;Khan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al () also found that chitosan coating did not significantly ( p > 0.05) decrease the weight loss of the sliced mushrooms packed in polyolefine films. Khan et al () observed gradual decrease in all treated samples (dipped in water, dipped in aqueous solution of 2.5% CaCl 2 and 0.5% citric acid and dipped in aqueous solution of 2.5% CaCl 2 and 0.5% citric acid and 3% sorbitol) during 12 days of storage at 12 °C and 90% ± 5 RH. The highest efficiency for inhibiting the weight loss was found in samples treated with CaCl 2 and citric acid.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the method to extend the durability and quality of products has become coatings (Khan et al, ). They are thin layers of materials applied to edible food products which play an important role in the maintenance, distribution, and marketing.…”
Section: Introductionmentioning
confidence: 99%